Research and Deployment Strategy of WCDMA Dual-Carrier Private Network in High-Speed Rail Abstract: The double（multiple）carrier private network is the only way to solve WCDMA network covering quality and user perception in the high-speed rail.As to ensure high-speed rail WCDMA network quality and user experience， the strategies such as neighboring configuration, key parameter strategy, business distribution, frequency reuse, fall back strategy and so on, were analyzed and discussed. It provides a basis and reference with the key issues and related strategies for the follow-up high-speed rail WCDMA network construction,planning,design and optimization. - Songbai Liang; Wensheng Li; Ning Wei; Wei Liu (Dianxin kexue)
The double（multiple）carrier private network is the only way to solve WCDMA network covering quality and user perception in the high-speed rail.As to ensure high-speed rail WCDMA network quality and user experience， the strategies such as neighboring configuration, key parameter strategy, business distribution, frequency reuse, fall back strategy and so on, were analyzed and discussed. It provides a basis and reference with the key issues and related strategies for the follow-up high-speed rail WCDMA network construction,planning,design and optimization.